The Influence of Knowledge Sharing and Organizational Culture on Job Satisfaction and Its Impact on Employee Performance - Makmur, Syukri; Marantika, Abshor; Zakaria, Nurman (Dinasti Publisher, 2025)
At the bureaucratic level, the use of information and communication technology has become a new trend, starting with the emergence of the issue of electronic government, namely electronic-based government. Currently, the ability of regional governments to develop, utilize and apply knowledge, including technology, is the key to successful development, so that the systematic development of regional innovation is very important and determines the success of the Communications, Informatics and Crypto Agency towards an economic era and a knowledgeable society. This research was conducted at the Communication, Informatics and Encryption Service, which is located on Jalan Jend.A.Yani NO.50 Bangkinang City. The aim of this research is to determine and analyze: 1) the effect of knowledge sharing on employee job satisfaction; 2) the direct influence of organizational culture on employee job satisfaction; 3) the direct influence of knowledge sharing on employee performance; 4) direct influence of organizational culture on employee performance; 5) the influence of job satisfaction on employee performance; 6) the direct influence of knowledge sharing on employee performance through job satisfaction and 7) the direct influence of organizational culture on employee performance through job satisfaction. The population of this study was all employees at the Kampar Regency Communication, Informatics and Encryption Service, totaling 35 people and all of them were used as samples. This research uses primary data and secondary data, which were obtained by conducting interviews, distributing questionnaires, observing and searching research files. The data analysis tool used is Structural Equation Modeling (SEM) and data processing is carried out using the SmartPLS version 3.0 program package. Hypothesis testing uses alpha 5%. The results of this research conclude that 1) knowledge sharing has been proven to have a significant effect on employee job satisfaction. 2) organizational culture is proven to have a significant effect on employee job satisfaction, 3) knowledge sharing is proven to have a significant direct effect on employee performance, 4) organizational culture is proven to have no direct significant effect on employee performance, 5) job satisfaction is proven to have a significant effect on employee performance, 6) knowledge sharing is proven to have a significant indirect effect on employee performance through job satisfaction, 7) organizational culture is proven to have a significant indirect effect on employee performance through job satisfaction